2022
DOI: 10.1021/acs.jafc.2c06650
|View full text |Cite
|
Sign up to set email alerts
|

Lycopene Alleviates Chronic Stress-Induced Liver Injury by Inhibiting Oxidative Stress-Mediated Endoplasmic Reticulum Stress Pathway Apoptosis in Rats

Abstract: The liver is the major organ of metabolism and is extremely vulnerable to chronic stress. Lycopene (LYC) is a natural carotenoid with potent antioxidant and chronic disease potential. However, whether LYC protects against chronic restraint stress (CRS)-induced liver injury and the underlying mechanisms remain unclear. In this study, rats were restrained for 21 days for 6 h per day, with or without gavage of LYC (10 mg/kg). Serum ALT (85.99 ± 4.07 U/L) and AST (181.78 ± 7.35 U/L) and scores of liver injury were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…These results suggest that ERS may be a potential mechanism of AEC senescence in IPF. Oxidative stress is one of the major drivers of protein homeostasis imbalance, which can lead to an increase in the number of unfolded proteins in the ER lumen, which in turn induces ERS [ 67 ]. Our previous study found that inhibition of EETs degradation has the ability to reduce the level of oxidative stress in the lungs [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that ERS may be a potential mechanism of AEC senescence in IPF. Oxidative stress is one of the major drivers of protein homeostasis imbalance, which can lead to an increase in the number of unfolded proteins in the ER lumen, which in turn induces ERS [ 67 ]. Our previous study found that inhibition of EETs degradation has the ability to reduce the level of oxidative stress in the lungs [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, this process triggers the activation of cleaved caspase3, initiating cell degradation [116]. This process holds a significant importance in the context of liver injury [117] since evidence suggested that the p53 protein accumulates in individuals with various inflammatory liver diseases. Inhibiting the p53 signaling pathway has been demonstrated to enhance drug-induced hepatocyte injury by regulating the mitochondrial apoptosis pathway.…”
Section: Discussionmentioning
confidence: 99%
“…SB203580 was solubilized in a combined solution made up of 10% DMSO, 40% PEG300, 5% Tween 80, and 45% saline. 22 All rats were fasted from food and water during the experiment (9:00−15:00). The body weight of the rats was checked every 3 days, and the amount of food taken by the rats was recorded daily.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…The CS + SB203580 group rats were given SB203580 (0.5 mg/kg, intraperitoneal injection, HY-10256, Med Chem Express, USA) 1 h before restraint stress every other day. SB203580 was solubilized in a combined solution made up of 10% DMSO, 40% PEG300, 5% Tween 80, and 45% saline . All rats were fasted from food and water during the experiment (9:00–15:00).…”
Section: Methodsmentioning
confidence: 99%